1988
DOI: 10.1111/j.1365-3032.1988.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory characteristics and sexual dimorphism in the gypsy moth

Abstract: ABSTRACT. The auditory characteristics of two populations (laboratory reared and wild) of North American gypsy moths (Lymantriidae: Lymantria dispar L.) were sampled and the neurally derived thresholds of wild males and females to frequencies from 5 to 150 kHz compared. The noctuoid auditory receptors, Al and A2‐cell, and putative proprioceptor, B‐cell, were identified. Both sexes possess neurally responsive ears but females exhibit median best frequencies significantly lower than those of males. Audiogram co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…Where there is sexual dimorphism in flight ability (flightless females, flight-capable males), males are at greater risk of bat predation, and females have less sensitive ears than males (Cardone and Fullard, 1988;Rydell et al, 1997). Interestingly, this relationship is also found in mantids (Yager, 1990).…”
Section: Nocturnal Activity Levelmentioning
confidence: 61%
“…Where there is sexual dimorphism in flight ability (flightless females, flight-capable males), males are at greater risk of bat predation, and females have less sensitive ears than males (Cardone and Fullard, 1988;Rydell et al, 1997). Interestingly, this relationship is also found in mantids (Yager, 1990).…”
Section: Nocturnal Activity Levelmentioning
confidence: 61%
“…In some hearing species flight is restricted to one gender, and sensitivity to ultrasound is reduced in the non-flying gender, e.g. moths (Cardone and Fullard, 1988) and mantises (Yager, 1990). These observations suggest that sensitivity to ultrasound is closely linked to flight physiologically, as well as evolutionarily.…”
mentioning
confidence: 71%
“…Female gypsy moths do not fly, whereas males do. Thresholds of auditory receptor neurons to ultrasonic frequencies are up to 20·dB higher in females than in males (Cardone and Fullard, 1988), despite any obvious difference in ear anatomy. In many mantis species only males fly, and ultrasound sensitivity of females, measured at the interneuron level, is reduced or absent (Yager, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…(1978), and, since the ears are responsive, Cardone & Fullard (1988) concluded that there must be a central nervous decoupling of the motor (behavioural) output from the sensory input. However, our results from the geometrids lead to the opposite conclusion, namely that the evasive behaviour persists as long as there is any remaining hearing ability.…”
Section: Discussionmentioning
confidence: 99%